HIV retesting and risk behaviors among high-risk, HIV-uninfected adults in Uganda. Issue 5 (4th May 2021) - Marson, Kara; Ndyabakira, Alex; Kwarisiima, Dalsone; Camlin, Carol S.; Kamya, Moses R.; Havlir, Diane; Thirumurthy, Harsha; Chamie, Gabriel
ABSTRACT: There are limited data characterizing HIV retesting among high-risk adults in sub-Saharan Africa. From October-December 2018, we distributed recruitment cards offering health evaluations with HIV testing at venues frequented by individuals at-risk of HIV infection in Southwest Uganda. Those who attended were asked about their HIV testing history and risk factors: having >1 sexual partner, an HIV+ partner, STIs, and/or transactional sex. We defined "highest risk" as ≥3 risk factors and "frequent testing" as ≥3 tests within the past year. Of 1, 777 cards distributed, 1, 482 (83%) adults came to clinic: median age was 26(IQR: 22-31), 598 (40%) were men, and 334 (23%) were HIV+. Of 1, 148 HIV-negative adults, 338 (29%) were highest risk and 205 (18%) were frequent testers. Frequent testing was similar in women (19%) and men (16%, p  = 0.22). Among women, those at highest risk were more likely to report any testing (90% vs. 81%, p  = 0.01) and frequent testing (25% vs. 18%, p  = 0.06) than those at lower risk. Among men, any testing and frequent testing were similar between risk levels. Among adults recruited from high-risk venues in peri-urban Uganda, HIV risk behaviors were commonly reported, yet frequent retesting remained low. Interventions to promote retesting are needed, particularly among men.